1997
DOI: 10.1017/s0016756897006882
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous use of thermal indicators to analyse the transition from diagenesis to metamorphism: an example from the Variscan Belt of northwest Spain

Abstract: The transition from diagenesis to very low-grade metamorphism has been characterized by conodont colour alteration index (CAI), illite crystallinity (IC), clay-mineral assemblages and rock fabric in a transect (Cape PeAas-Cape Torres) located in the Cantabrian Zone (northwest Spain). IC values show a northwest to southeast change from epizonal to diagenetic values. CAI values show a general congruence for low-and high-grade areas. This correlation indicates that CAI values for the epizone are > 5.5, the anchiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
(20 reference statements)
0
31
1
Order By: Relevance
“…However, low-grade metamorphism developed locally (Aller & Brime 1985, Aller 1986, Raven & Van der Pluijm 1986, Colmenero & Prado 1993, García-López et al 1997, Brime et al 2001, Frings et al 2004. Two distinct metamorphic events affected the CZ.…”
Section: Geological Settingmentioning
confidence: 99%
“…However, low-grade metamorphism developed locally (Aller & Brime 1985, Aller 1986, Raven & Van der Pluijm 1986, Colmenero & Prado 1993, García-López et al 1997, Brime et al 2001, Frings et al 2004. Two distinct metamorphic events affected the CZ.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Permian heating phase in the Sabero Coalfield (Fig. 3) was probably caused by the well-known magmatism and its associated hydrothermal activity under an extensional tectonic regime (Aller et al 2005;García-López et al 1997, 2007. The important heating phase had a significant thermal effect due to a deep source of heat.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, new models (Fig. 3) were constructed taking into account previous thermal history studies in the SCZ (García-López et al 1997, 2007Ayllon 2003;Ayllon et al 2003;Frings et al 2004;Aller et al 2005;Frings and Warr 2012;Botor 2012), which indicated that the Late Carboniferous-Permian period was the main heating time. Vitrinite reflectance data were used to calculate the maximum palaeotemperatures (values T max 2 and T max 3 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations